25 years - Lucio Cruz (Raton Range Raton, New Mexico, 1989)
Newspaper Article on the retirement of City employee Lucio Cruz of Raton, New Mexico.
Master list item #: 36
File location is in the Raton File Cabinet
Keywords: Cruz, Lucio; Baker, Mickey; Local History; Biography; Life and Customs; Retirement; Celebration; Raton, New Mexico